The Impact of the COVID-19 Lockdown Level 5 on Workers: 35 Days that Shook Workers of South Africa. Issue 3 (1st July 2022) - Hlatshwayo, Mondli
ABSTRACT: Built on Internet-based research, this article traverses the less-charted terrain of the impact of COVID-19 on workers within South Africa during the country's level 5 lockdown, which began on 26 March 2020 and ended on 30 April 2020. It reveals that the post-apartheid state's adoption of austerity measures—which began in the 1990s—hampered efforts to meaningfully protect workers' lives and livelihoods during the lockdown. The post-1994 African National Congress (ANC) government's neoliberal neglect of public health, housing and transportation made it next to impossible for the state to confront the virus, a challenge that required working and reliable infrastructure. Despite all these adversities, and in the general absence of the unions that were prevented from operating during lockdown level 5, workers resisted and demanded improved health and safety for themselves, better working conditions and access to transportation during the level 5 lockdown.